The influence of highly-purified olive polyphenols and special diets on cognition and brain mitochondrial function during the physiological aging process in mice - Reutzel, Martina Annika; Justus Liebig University Giessen (My University, 2020)
Alzheimer´s disease, a multifactorial chronic disease, is one of the most common causes of dementia, accounting for 60-80% of all cases, and has advanced age as a major risk factor. The aging process at the molecular level here shows mitochondrial dysfunction, which is characterized by the decline of cellular ATP levels, reduced mitochondrial respiration and a decrease in mitochondrial biogenesis. At the outset, a cohort of 3-week-old female NMRI mice was examined over a 24-month period at 6-month intervals for various parameters designed to provide insight into changes during the physiological aging process. Comprehensive characterization of this mouse strain revealed that the first measurable deficits in the cognitive domain appeared as early as 12 months of age, which could be observed in the Y-Maze test, a marker of spatial memory and motor function. Energy levels in the brain were also stable up to 18 months of age, whereas mitochondrial respiration showed first deficits of respiratory chain complexes I and IV already at 12 months of age. Mitochondrial membrane potential (MMP), the driving force for ATP synthesis, did not show a significant decrease until 24 months of age compared with young control mice. With these results, the effect of an aqueous mixture of highly purified olive polyphenols and two secoridiod derivatives as pure substances (ligstroside, oleocanthal) on the physiological aging process in NMRI mice was investigated in the further course of this work as part of a BMBF-funded project. The aqueous extract of olive polyphenols and the two pure substances showed positive effects on cognitive performance and basal brain ATP levels in 18-month-old NMRI mice after 6 months of feeding.Next, the effect of different standard rodent diets on brain energy metabolism and cognition during physiological aging was investigated. For this purpose, an antioxidant-reduced and two different high-fat diets were studied with respect to cognition and mitochondrial influences in mice. Here, it was shown that a diet free of vitamin C and simultaneously reduced in vitamin E had moderate effects in the Y-Maze test after 6 months of feeding in aged NMRI mice and resulted in an increase in basal ATP levels in dissociated brain cells (DBC´s) of the mice. The 70% high-fat diet in C57Bl/6J mice also showed a significant increase in ATP levels in the brains of the mice.
Der Einfluss von hochreinen Olivenpolyphenolen und Spezialdiäten auf die mitochondriale Gehirnfunktion während des physiologischen Alterungsprozesses in Mäusen
Keywords: ddc:640